FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA PEGAWAI NEGERI SIPIL DI KOTA BEKASI - Dian Anggraeni Rahim (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
The purpose of this research is to find out what influence factors of job satisfaction for the government emplorees at Bekasi City The data is collected by distributing questionnaires to 105 respondents of the employees at Bekasi City, based on random sampling. The analytical tool for this research is analysis factor. The results shows that, from the 20 variables, there are 5 factors is formed with the highest eigenvalue, which is organizational culture , how to work, work condition, communication and work supervision.